2005
DOI: 10.1007/s00405-005-0982-6
|View full text |Cite
|
Sign up to set email alerts
|

Neck mass as the first presentation of testicular choriocarcinoma

Abstract: Choriocarcinoma is a highly malignant tumor of the testis and usually occurs as a component of mixed germ cell tumor. The testicular enlargement may be subtle, and the patient may present with metastasis, the neck being one of its least reported locations. A case of testicular choriocarcinoma in a 24-year-old man who presented for the first time with metastatic neck mass is reported here. This presentation, although very rare, can be a great diagnostic and therapeutic challenge and should be considered in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…2 The most common sites of metastasis of testicular germ cell tumors are the retroperitoneal lymph nodes, lungs, and liver. 2,3 • In 1973, Flocks and Boatman categorized genitourinary malignancies according to the incidence of head and neck metastasis. 15 They found that 13% of testicular malignancies metastasized to the head and neck region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 The most common sites of metastasis of testicular germ cell tumors are the retroperitoneal lymph nodes, lungs, and liver. 2,3 • In 1973, Flocks and Boatman categorized genitourinary malignancies according to the incidence of head and neck metastasis. 15 They found that 13% of testicular malignancies metastasized to the head and neck region.…”
Section: Discussionmentioning
confidence: 99%
“…1 Choriocarcinoma is a rare, highly malignant tumor of the testes, and it usually occurs as a component of mixed germ cell tumor. 3 The incidence of testicular carcinoma metastatic to the neck has been reported to be 5%. 3 Even more uncommon is a finding of choriocarcinoma as a neck mass without any sign of a primary testicular tumor, as only a few such cases have been published in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the second case from Zangana et al 5 reported a pure teratoma with a smaller mass size. There are few reports of subcutaneous metastasis from germ cell tumours in general, with some authors suggesting that subcutaneous tissue could be the primary [6][7][8] origin of these germ cell tumours. [9][10][11] In addition to reporting this unusual presentation, we also stress upon two other observations.…”
Section: Discussionmentioning
confidence: 99%
“…Choriocarcinoma is a highly malignant uncommon tumor of the testis, and it usually occurs as a component of mixed germ cell tumor (1). The testicular enlargement may be subtle, and the patient may present with multiple metastasis.…”
Section: Introductionmentioning
confidence: 99%